Using hot-spot-driven approach in the development of a framework for multimedia presentation on the Web - Al-Tahat K.S.; Idris S.B.; Sembok T.Mohd.T.; Yousof M. (ICEIS Press, 2023)
Frameworks can be seen as generative since they are intended and well suited to be used as the foundation for the development of a number of applications in the domain captured by the framework. A framework defines a high-level language with which applications within a domain are created through specialization. Specialization takes place at points of predefined refinement that are called hot spots. Hot spots are the generic and flexible aspects and parts of a framework that can be easily adapted to a specific need. Specialization is accomplished through inheritance or composition. Well-designed framework offers the domain-specification hot spots and the desired flexibility to adapt those hot spots. Hot spots are shown by hook methods and hook classes, where metapatterns express how the required flexibility, represented by the hot spots, is gained in a particular framework. We have adopted the hot-spot approach in the development of a framework for multimedia presentation on the Web. The adoption of this approach has helped us in enhancing the flexibility and extensibility of the framework. This paper describes the use of a hot-spotdriven approach in the development of a framework for multimedia presentation on the Web as well as our experience in using hot spots, design patterns, and metapatterns.